Empirical investigation on the dependence of TCP downstream throughput on SNR in an IEEE802.11b WLAN system - Ikponmwosa Oghogho; Fredrick O. Edeko; Joy Emagbetere (Journal of King Saud University: Engineering Sciences)
The dependence of TCP downstream throughput (TCPdownT) on signal to noise ratio (SNR) in an IEEE802.11b WLAN system was investigated in various environments and varieties of QoS traffic. TCPdownT was measured for various SNR observed. An Infrastructure based IEEE802.11b WLAN system having networked computers on which measurement software were installed, was set up consecutively in various environments (open corridor, small offices with block walls and plaster boards and free space). Empirical models describing TCPdownT against SNR for different signal ranges (all ranges of signals, strong signals only, grey signals only and weak signals only) were statistically generated and validated. As the SNR values changed from high (strong signals) through low (grey signals) to very low (weak signals), our results show a strong dependence of TCPdownT on the received SNR. Our models showed lower RMS errors when compared with other similar models. We observed RMS errors of 0.6734791 Mbps, 0.472209 Mbps, 0.9111563 Mbps and 0.5764460 Mbps for general (all SNR) model, strong signals model, grey signals model and Weak signals model respectively. Our models will provide researchers and WLAN systems users with a tool to estimate the TCP downstream throughput in a real network in various environments by monitoring the received SNR.